2013
DOI: 10.1089/ten.tea.2012.0425
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization alters phenotype, maintains plasticity of pre-differentiated mesenchymal stem cells

Abstract: Although adult stem cell transplantation has been implemented as a therapy for tissue repair, it is limited by the availability of functional adult stem cells. A potential approach to generate stem and progenitor cells may be to modulate the differentiated status of somatic cells. Therefore, there is a need for a better understanding of how the differentiated phenotype of mature cells is regulated. We hypothesize that bioelectric signaling plays an important role in the maintenance of the differentiated state,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…[47][48][49][50][51][52][53][54][55] In terms of stem cell state, undifferentiated stem cells with greater proliferative capacity (than their differentiated progeny) have been suggested to be associated with a depolarized plasma membrane, while terminally differentiated and quiescent cells tend to be hyperpolarized. 53 This relationship may be true for hMSCs as well; modulation of plasma membrane potential via pharmaceuticals or changing the ionic milieu has been shown to be able to override biochemical signaling to prevent hMSC differentiation, 47 or suppress their differentiated state, 56 even in the presence of the most potent chemical mediators known to drive differentiation down certain lineages. In addition, mitochondrial membrane potential may also be involved in differentiation and immunomodulatory functions of hMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53][54][55] In terms of stem cell state, undifferentiated stem cells with greater proliferative capacity (than their differentiated progeny) have been suggested to be associated with a depolarized plasma membrane, while terminally differentiated and quiescent cells tend to be hyperpolarized. 53 This relationship may be true for hMSCs as well; modulation of plasma membrane potential via pharmaceuticals or changing the ionic milieu has been shown to be able to override biochemical signaling to prevent hMSC differentiation, 47 or suppress their differentiated state, 56 even in the presence of the most potent chemical mediators known to drive differentiation down certain lineages. In addition, mitochondrial membrane potential may also be involved in differentiation and immunomodulatory functions of hMSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The combined actions of ion channels and transporters establish membrane potentials by regulating intracellular and extracellular ionic concentrations 10, 11 . Increasing evidence suggests that membrane potentials are not only involved in the cellular processes of proliferation, migration and differentiation 1214 , but are also related to complex processes such as control of wound healing 15, 16 , regeneration 17, 18 , left-right patterning 19 and development 15 . Thus, it is suggested that membrane potentials are a fundamental control mechanism of cell functions 10 .…”
Section: Introductionmentioning
confidence: 99%